1997
DOI: 10.1164/ajrccm.156.6.9611016
|View full text |Cite
|
Sign up to set email alerts
|

Airway Smooth Muscle, Tidal Stretches, and Dynamically Determined Contractile States

Abstract: In the classic theory of airway lumen narrowing in asthma, active force in airway smooth muscle is presumed to be in static mechanical equilibrium with the external load against which the muscle has shortened. This theory is useful because it identifies the static equilibrium length toward which activated airway smooth muscle would tend if given enough time. The corresponding state toward which myosin-actin interactions would tend is called the latch state. But are the concepts of a static mechanical equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
377
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(416 citation statements)
references
References 48 publications
35
377
2
2
Order By: Relevance
“…The finding of study 1 that the deep breaths blunted the decrease of FEV 1 and FVC but not of measurements not preceded by a full inflation, such as V part, RVpart, FRC, and sGaw, suggests a mechanism facilitating the distensibility of contracted airways rather than inhibiting airway smooth muscle shortening. In healthy subjects, the disappearance of the effect of prior deep breaths on the decrease of FEV 1 and FVC after 10 min of prohibition of further deep breaths may reflect a progressive increase in airway smooth muscle stiffness when the contractile apparatus is no more urged to change configuration with large lung inflations (3,5). This is consistent with in vitro data showing that the tone of airway smooth muscle is fully recovered under static conditions within 8 min after a large stretch (4).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The finding of study 1 that the deep breaths blunted the decrease of FEV 1 and FVC but not of measurements not preceded by a full inflation, such as V part, RVpart, FRC, and sGaw, suggests a mechanism facilitating the distensibility of contracted airways rather than inhibiting airway smooth muscle shortening. In healthy subjects, the disappearance of the effect of prior deep breaths on the decrease of FEV 1 and FVC after 10 min of prohibition of further deep breaths may reflect a progressive increase in airway smooth muscle stiffness when the contractile apparatus is no more urged to change configuration with large lung inflations (3,5). This is consistent with in vitro data showing that the tone of airway smooth muscle is fully recovered under static conditions within 8 min after a large stretch (4).…”
Section: Discussionsupporting
confidence: 80%
“…The difference in the effect of the deep breaths on FEV 1 and FVC between healthy and asthmatic subjects, but not on the parameters not preceded by a full inflation, may be interpreted as reflecting greater airway stiffness in asthma (7,8). According to the latch-bridge theory (15), unstretched airway smooth muscle goes into a "frozen" state characterized by less hysteresivity and greater stiffness (3). Therefore, a reduced ability of the full inflations to distend constricted airways would reflect a greater proportion of latch bridges formed in asthma during prohibition of the deep inspirations preceding MCh inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a brief, transient force increase leads to a long-lasting lengthening of the muscle, and a brief, transient length increase leads to a long-lasting force reduction and softening of the muscle. These model predictions have been qualitatively confirmed in numerous smooth muscle studies [2][3][4][5]8].…”
Section: Acto-myosin Bridge Dynamicssupporting
confidence: 62%
“…Such a force balance need not be static in the sense that the degree of airway constriction reaches a steadystate, and indeed, over the past decade numerous experimental and theoretical studies have shown that airway caliber is equilibrated dynamically rather than statically [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Indeed, the force-length curve of activated smooth muscle is constantly changing as the muscle adapts to its mechanical surroundings, such as the length to which it is stretched or the load against which it must contract.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly ASM is known to exhibit different behavior when forced at higher frequencies (29), and airway-ASM coupling on shorter timescales is certainly an area worth investigating more carefully; for example, FIGURE 5 Changes in pressure-radius hysteresis curves, using the implied tension transfer function, as ASM activation is varied for fixed order (left) and as airway order is varied for fixed activation (right). Color coding as in Fig.…”
Section: Discussionmentioning
confidence: 99%